Smart Chimeric Lysin ClyC Loaded Alginate Hydrogel Reduces Staphylococcus aureus Induced Bone Infection - Yao, Fangfang; Wu, Xinyu; Liao, Yilin; Yan, Qi; Li, Yuhong (Frontiers in Materials, 2021)
Staphylococcus aureus (S. aureus) is the most common cause of hospital and community-acquired infections. The current clinical treatment is limited by the emergence of drug-resistant strains. We previously developed a chimeric ClyC that effectively inhibited S. aureus strains. Nonetheless, an efficient delivery system to provide sustained release of ClyC to infected site is needed. Thus, we engineered a chimeric ClyC loaded alginate hydrogel (ClyC-AH) to improve the therapeutic outcome against S. aureus. ClyC-AH retained the stability and activity of ClyC while providing a sustained release of ClyC and a continuous antibacterial effect against S. aureus. Compared to ClyC alone, the use of ClyC-AH was relatively safe, as there was no significant cytotoxicity to BHK-21 cells at a ClyC concentration≤250 μg/mL. Furthermore, in a S. aureus infected mouse model of osteomyelitis, ClyC-AH reduced bacterial burden in the femur and surrounding tissues, with a reduction of 2 log10 (CFU/mL) in viable bacterial number. Based on these results, hydrogel-delivered chimeric lysin ClyC provides a promising future in the S.aureus targeting therapy.